Análisis de impactos socio-ambientales para el diseño y construcción de líneas de transmisión eléctrica de 69 kv, 138 kv y 230 kv. - Zurita Pacheco, Cristian Paúl (2020)
This research project was carried out in order to determine and analyze socio-environmental impacts produced by Electric Transmission Lines of different voltages 69 Kv, 138 Kv and 230 Kv, in projects generated by Electric energy in Ecuador to satisfy different needs to bring well-being and economic development to all regions of the country, exponential growth of infrastructure projects have been applied, among transport and distribution of electricity stands out since it is one of the most important inputs for The humanity. However, electrical transmission lines modify the environment, landscape and natural habitats, becoming a threat to biodiversity conservation, especially groups as flora and fauna to their exposure or direct mortality risk from these structures In order to counteract negative effects or impacts, series of environmental strategies have been used to minimize socio-environmental impacts produced by this activity. These experiences consist of the application of different practices or measures to avoid collisions and disorientation in native animals, deter mammals, management of vegetation in the areas under the line in order to protect the soil, increase the number of pollinators and avoid the introduction of invasive species among others. The obtained results from the research on socio-environmental impacts were bibliographic and qualitative, where several negative impacts were identified towards environment and society, having as a result that they affect the quality of the soil, flora, fauna, landscape, through the loss of soil fertility and general properties, fauna with deaths of different species or migration to other places, flora with the loss of native species in the area. The purpose of this project was to determine different applicable environmental and social strategies through the development of a guide or a manual, to counteract negative effects produced by electrical transmission lines on fauna, flora, and society to conserve Natural Resources and improve the quality of life of general population.